Інформаційна технологія дослідження стоку вуглецю в лісових екосистемах - Токар, Ольга Євгенівна (Національний університет "Львівська політехніка", 2015)
У дисертаційній роботі розв’язано актуальне наукове завдання розроблення інформаційної технології для обчислення стоку та запасів вуглецю в лісових екосистемах. Розроблено інформаційну технологію визначення запасів вуглецю лісових екосистем на рівні елементарних об’єктів із використанням математичних моделей, які враховують територіальну специфіку, що дало змогу підвищити точність оцінки запасів вуглецю у всіх резервуарах лісових екосистем. Розроблено багаторівневу модель стоку вуглецю в лісові екосистеми, яка базуються на принципі агрегації даних статистичної інвентаризації до рівня регіону, що дало можливість врахувати специфіку регіональних статистичних даних. Удосконалено математичні моделі запасів вуглецю для різних резервуарів ієрархічної лісової системи, які враховують регіональні особливості лісових екосистем, що забезпечило підвищення точності оцінки запасів вуглецю у лісовій екосистемі. Удосконалено метод просторової інвентаризації вуглецю в лісових екосистемах завдяки використанню точкових джерел стоків та вибору оптимальної моделі ходу росту деревостанів, що дало змогу враховувати специфіку процесів поглинання вуглецю на різних рівнях деталізації. В диссертационной работе решено актуальное научное задание разработки информационной технологии для вычисления стока и запасов углерода в лесных экосистемах. Разработана информационная технология определения запасов углерода лесных экосистем на уровне элементарных объектов с использованием математических моделей, которые учитывают территориальную специфику, что позволило повысить точность оценки запасов углерода во всех резервуарах лесных экосистем. Разработана многоуровнева модель стока углерода в лесные экосистемы, основана на принципе агрегации данных статистической инвентаризации до уровня региона, что позволило учесть специфику региональных статистических данных. Усовершенствованы математические модели запасов углерода для различных резервуаров иерархической лесной системы, учитывающих региональные особенности лесных экосистем, что обеспечило повышение точности оценки запасов углерода в лесной экосистеме. Усовершенствован метод пространственной инвентаризации углерода в лесных экосистемах, за счет использования точечных источников стоков и выбора оптимальной модели хода роста древостоев, что позволило учитывать специфику процессов поглощения углерода на различных уровнях детализации. The thesis solves an actual research task on development of an information technology for estimation of carbon sink and carbon stocks in forest ecosystems. An information technology for estimation of carbon stocks in phytomass, dead organic matter and soil organic matter of forest ecosystems has been developed. The information technology is based on consideration of elementary objects (individual trees) and region-specific mathematical models that allows to improve accuracy of the estimates of carbon stocks in all carbon pools of forest ecosystems. A multi-level model of carbon sink in forest ecosystems has been developed. The model is based on aggregation of results of statistical inventory within an administrative region that allows taking into account peculiarities of regional statistics. The information technology includes interpretation of input data of the statistical inventory of forest stands using digital maps of forests, forming databases and data processing by applying a special algorithm for calculating carbon sink in forest ecosystems and presenting the results in a form of thematic maps. The estimation of carbon sink in forest ecosystems is based on a bottom-up approach (tree – experimental plot – forestry) using mathematical models for georeferenced inventory of carbon sink which take into account tree species composition and mean annual increment. Carbon sink in stem wood has been estimated using developed model and measurement data from 54 experimental plots of forest enterprises “Spaske” and “Broshnivske LG” from the Ivano-Frankivsk Region of Ukraine. The information technology can be applied for estimation of carbon sinks in stem wood any region in Ukraine if necessary input data are available. Mathematical models for estimation of carbon stocks in different pools of forest ecosystem have been improved by taking into account regional peculiarities of the forest ecosystems that decreases uncertainty of the estimate. Carbon stocks in aboveground and belowground biomass, litter, dead organic matted and soil organic matter (by 50 cm depth) have been estimated using the improved models. A method of georeferenced carbon inventory in forest ecosystems has been improved by applying single-tree accounting and selecting an optimal forest growth model that allows accounting for peculiarities of carbon sink processes on different scales. A GIS technology for analysis of carbon sinks in forest ecosystems and developing georeferenced carbon inventories has been developed.
Информационная технология исследования стока углерода в лесных экосистемах
Information technology for studying carbon sink in forest ecosystems
Keywords: інформаційна технологія; лісова екосистема; статистична інвентаризація; математична модель; стік вуглецю; запас вуглецю; информационная технология; лесная экосистема; статистическая инвентаризация; математическая модель; сток углерода; запас углерода; information technology; forest ecosystem; statistical inventory; mathematical model; carbon sink; carbon stock